Combination of Pirfenidone and Andrographolide Ameliorates Hepatic Stellate Cell Activation and Liver Fibrosis by Mediating TGF-β/Smad Signaling Pathway - Guang Xu; Tidong Ma; Chonggao Zhou; Fan Zhao; Kun Peng; Bixiang Li (Analytical Cellular Pathology)
Background. Biliary atresia (BA) is a devastating congenital disease characterized by inflammation and progressive liver fibrosis. Activation of hepatic stellate cells (HSCs) plays a central role in the pathogenesis of hepatic fibrosis. Our study aimed to investigate the pharmacological effect and potential mechanism of pirfenidone (PFD) and andrographolide (AGP) separately and together on liver fibrosis of BA. Materials and Methods. The bile ducts of male C57BL/6J mice were ligated or had the sham operation. The in vivo effects of PFD and/or AGP on liver fibrosis of BA were evaluated. Human hepatic stellate cells (LX-2) were also treated with PFD and/or AGP in vitro. Results. PFD and/or AGP ameliorates liver fibrosis and inflammation in the mice model of BA, as evidenced by significant downregulated in the accumulation of collagen fibers, hepatic fibrosis markers (α-SMA, collagen I, and collagen IV), and inflammatory markers (IL-1β, IL-6, and TNF-α). Moreover, compared with monotherapy, these changes are more obvious in the combined treatment of PFD and AGP. Consistent with animal experiments, hepatic fibrosis markers (α-SMA, collagen I, and CTGF) and inflammatory markers (IL-1β, IL-6, and TNF-α) were significantly decreased in activated LX-2 cells after PFD and/or AGP treatment. In addition, PFD and/or AGP inhibited the activation of HSCs by blocking the TGF-β/Smad signaling pathway, and the combined treatment of PFD and AGP synergistically inhibited the phosphorylation of Smad2 and Smad3. Conclusion. The combined application of PFD and AGP exerted superior inhibitive effects on HSC activation and liver fibrosis by mediating the TGF-β/Smad signaling pathway as compared to monotherapy. Therefore, the combination of PFD and AGP may be a promising treatment strategy for liver fibrosis in BA.